Physicochemical Characterization of a liquid Effluent from a Refinery - J.O. Osuoha; E.O. Nwaichi (Journal of Applied Sciences and Environmental Management, 2019)
The physicochemical profile of wastewater from a Refinery in the Niger Delta was evaluated to ascertain efficiency of wastewater treatment methods applied using standard analytical methods. In all samples, temperature ranged between 26.45 – 28.65 º C while the pH values of the untreated and treated wastewater samples were 8.39 ± 0.04 and 7. 82 ± 0.02 respectively. Total dissolved solids and observed total hydrocarbon levels gave maximum values of 172 mg/L and 11.35 mg/L respectively. The turbidity values for untreated and treated wastewater samples were 7.55 ± 0.08 and 3.49 ± 0.01 NTU respectively. The results revealed that the untreated wastewater sample had a higher concentration of phenol (28.46 ± 1.23) when compared to those (9.34 ± 0.89) of the treated wastewater sample while the cyanide content was relatively higher when compared to the limits set by World Health Organization for such effluents. Although substantial improvements were obvious in some water quality indices with treatment, high concentration of major effluent pollutants, phenol and total hydrocarbon content in the treated wastewater is indication of ineptitude in the effluent management system and calls for immediate intervention